2014
DOI: 10.1371/journal.pone.0107701
|View full text |Cite
|
Sign up to set email alerts
|

A Census Tract–Level Examination of Social Determinants of Health among Black/African American Men with Diagnosed HIV Infection, 2005–2009—17 US Areas

Abstract: BackgroundHIV disproportionately affects black men in the United States: most diagnoses are for black gay, bisexual, and other men who have sex with men (collectively referred to as MSM). A better understanding of the social conditions in which black men live and work may better explain why HIV incidence and diagnosis rates are higher than expected in this population.MethodsUsing data from the National HIV Surveillance System and the US Census Bureau's American Community Survey, we examined the relationships o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 33 publications
2
27
1
Order By: Relevance
“…In DC, HIV prevalence was significantly higher among those with lower education, unemployment, and incarceration history and in both DC and Philadelphia, those with public insurance were substantially more likely to be HIV-positive. These findings support previous research that shows a connection between high poverty, low education and elevated HIV prevalence among BMSM 6 and make clear .the importance of employing a social determinants perspective in HIV planning for BMSM, as others have noted. 4,25 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In DC, HIV prevalence was significantly higher among those with lower education, unemployment, and incarceration history and in both DC and Philadelphia, those with public insurance were substantially more likely to be HIV-positive. These findings support previous research that shows a connection between high poverty, low education and elevated HIV prevalence among BMSM 6 and make clear .the importance of employing a social determinants perspective in HIV planning for BMSM, as others have noted. 4,25 …”
Section: Discussionsupporting
confidence: 91%
“…At the same time, population differences at multiple levels as well as local context influence lifetime risk of HIV exposure and transmission risk among BMSM. 5,6,1 There is a lack of understanding of the complex interplay between prevailing and local factors in the HIV epidemic among BMSM and a dearth of comprehensive HIV interventions for BMSM 7 . These gaps undermine municipal ability to effectively address regional and local HIV transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Observed racial disparities might result from underlying patient-level disparities, such as differences in underlying health, access to medical care, health-seeking behavior, and environmental factors [20, 21]. For example, our data showed that blacks with invasive MRSA associated with healthcare exposure (HO and HACO cases) had more documented chronic medical comorbidities than whites.…”
Section: Discussionmentioning
confidence: 85%
“…; Gant et al . ). However, they are not designed for investigating such data, and their use may produce misleading and inaccurate results (Shortt ).…”
Section: Introductionmentioning
confidence: 97%
“…The analysis of health and social data requires consistent geographical units of analysis in order to make fair comparisons between areas. Historically, researchers and policy analysts have used readily available census and administrative boundaries to report small-area or 'neighbourhood' statistics (Pearce et al 2006a,b;Greer et al 2010;Gant et al 2014). However, they are not designed for investigating such data, and their use may produce misleading and inaccurate results (Shortt 2009).…”
Section: Introductionmentioning
confidence: 99%